Amphiphilic binder for silicon-based negative electrode of lithium ion battery as well as preparation method and application of amphiphilic binder

By using palliative binders synthesized by lipoic acid, tannin acid and 1-pyrene-methylammonium hydrochloride, the problem of insufficient volume expansion and bonding performance of silicon carbon anode material for lithium-ion batteries is solved, and the electrochemistry of the battery is significantly improved Performance and cycle stability.

CN119432309AActive Publication Date: 2025-02-14GUANGDONG UNIV OF TECH +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411362332.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-02-14
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The existing silicon carbon anode materials for lithium-ion batteries have volume expansion problems, resulting in poor cycle stability and rate performance, and the commonly used negative electrode binders are difficult to effectively disperse the silicon carbon material and form a good bond with copper foil.

Method used

The amphiphilic binder prepared by amidation reaction with 1-pyrene methamic hydrochloride after reacting lipoic acid and tanninic acid through polyphenol-thio radical addition, the binder has a three-dimensional network structure and Good affinity can effectively disperse and protect silicon-carbon materials.

Benefits of technology

The electrochemical performance of the silicon-based anode of lithium-ion batteries is significantly improved, including improving cycle stability and first-time Coulomb efficiency, reducing the generation of SEI films, and enhancing the mechanical properties of the silicon-carbon anode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432309A_ABST
    Figure CN119432309A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium batteries, and discloses an amphiphilic binder for a silicon-based negative electrode of a lithium ion battery and a preparation method and application thereof.The amphiphilic binder is abbreviated as PLT-Y. The preparation method comprises the steps that in the nitrogen atmosphere, lipoic acid and tannic acid are heated and stirred at the temperature of 120-150 DEG C, after an obtained mixed solution is dissolved in N, N-dimethylformamide, the mixed solution is heated and stirred at the temperature of 120-150 DEG C, and then the amphiphilic binder is obtained; then sequentially adding benzotriazole-1-yl-oxytripyrrolidinophosphate hexafluorophosphate, triethylamine and 1-pyrene methylamine hydrochloride, carrying out amidation reaction at room temperature, then pouring into deionized water to separate out precipitate, and finally freeze-drying to obtain the compound. The amphiphilic binder has the advantages of good dispersibility, strong cohesiveness and the like on a silicon-based material, and can effectively inhibit volume expansion of a silicon-carbon negative electrode material in the charging and discharging process of an electrode, so that the silicon-carbon negative electrode shows good cycling stability, and the electrochemical performance of the silicon-based negative electrode of the lithium ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular, relates to an amphiphilic binder for a silicon-based negative electrode of a lithium-ion battery, and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have the advantages of high capacity, no memory effect, fast reversible charge and discharge, and high coulombic efficiency. Lithium-ion batteries are currently widely used in commercial products such as mobile phones, laptops, digital cameras, new energy vehicles, etc. Graphite is a common negative electrode material for lithium-ion batteries. However, as the energy density of lithium-ion batteries continues to increase, the graphite negative electrode with a theoretical capacity of only 372mAh / g cannot meet the existing needs. Therefore, there is an urgent need to find a high-capacity negative electrode material that can replace graphite. Among the many new negative electrode materials, silicon is considered to be the most promising new generation of negative electrode materials, with a theoretical capacity of up to 4200mAh / g. However, due to the huge volume change (about 300%) and low first coulombic efficiency of silicon-based negative electrode materials, their commercialization is seriously hindered. Silicon-carbon materials with better cycle performance and higher coulombic efficiency are currently the hot spots for the commercialization of silicon-based materials, but silicon-carbon materials still have certain volume expansion problems, which leads to their poor long-cycle stability and rate performance.

[0003] At present, the main methods to solve the volume expansion problem of silicon-carbon negative electrodes include nano-sizing and structuring. Due to the complex synthesis process, cumbersome steps and high cost, it is difficult to achieve commercialization. Through research and investigation, optimizing the binder is one of the most economical and effective methods to solve the volume expansion problem of silicon-carbon negative electrodes. The main functions of the negative electrode binder are: bonding the negative electrode material and the negative electrode material and the current collector to stabilize the structure; acting as a dispersant when making the negative electrode slurry to reduce material agglomeration. Due to the complexity of silicon-carbon materials, the currently commonly used negative electrode binders (CMC and SBR) are difficult to disperse silicon-carbon materials during the slurrying process. At the same time, due to poor affinity, the bonding force between the material and the copper foil is poor and it is easy to fall off. Therefore, the current commercial binders are not suitable for silicon-carbon negative electrodes. In recent years, researchers have made great efforts in the design and preparation of silicon-carbon binders, and improved the electrochemical performance of silicon-carbon negative electrodes by synthesizing functionalized binders. Summary of the invention

[0004] In order to solve the above-mentioned deficiencies and shortcomings of the prior art, the primary purpose of the present invention is to provide an amphiphilic binder for a silicon-based negative electrode of a lithium-ion battery. The binder has the advantages of good dispersibility and strong adhesion to silicon-carbon materials, and can effectively inhibit the volume expansion of silicon-carbon negative electrode materials during the charge and discharge process of the electrode, so that the silicon-carbon negative electrode exhibits good cycle stability, and significantly improves the electrochemical performance of the silicon-based negative electrode of the lithium-ion battery.

[0005] Another object of the present invention is to provide a method for preparing the above-mentioned amphiphilic binder for the silicon-based negative electrode of a lithium ion battery. The method is to initiate ring-opening polymerization of lipoic acid by heating to obtain linear polylipoic acid, then undergo polyphenol-sulfenyl free radical addition reaction with tannic acid to obtain polylipoic acid-tannic acid, and then undergo amidation reaction with 1-pyrenecarboxamine hydrochloride to synthesize the amphiphilic binder, the preparation process is simple and the cost is low.

[0006] Another object of the present invention is to provide an application of the above-mentioned amphiphilic binder for silicon-based negative electrodes of lithium-ion batteries.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] The invention discloses an amphiphilic binder for a silicon-based negative electrode of a lithium-ion battery. The amphiphilic binder is abbreviated as PLT-Y. In a nitrogen atmosphere, lipoic acid and tannic acid are heated and stirred at 120-150° C. The obtained mixed solution is dissolved in N,N-dimethylformamide, and then benzotriazole-1-yl-oxytripyrrolidinophosphine hexafluorophosphate (PyBOP), triethylamine and 1-pyrenecarboxamine hydrochloride are added in sequence. After an amidation reaction at room temperature, the mixture is poured into deionized water to precipitate, and finally freeze-dried to obtain the amphiphilic binder.

[0009] Preferably, the mass ratio of the lipoic acid, tannic acid, benzotriazole-1-yl-oxytripyrrolidinophosphine hexafluorophosphate and 1-pyrenecarboxamine hydrochloride is 1:(0.04-0.12):(0.2-0.36):(0.12-0.4); the mass ratio of the lipoic acid to triethylamine is 1 g:(0.08-0.15) mL.

[0010] Preferably, the heating and stirring time is 0.5 to 2 hours, the amidation reaction time is 6 to 36 hours, and the freeze-drying time is 12 to 36 hours.

[0011] The method for preparing the amphiphilic binder for the silicon-based negative electrode of a lithium-ion battery comprises the following steps:

[0012] S1. In a nitrogen atmosphere, lipoic acid is heated and stirred at 120-150° C., and then tannic acid is added to cause a cross-linking reaction, cooled at room temperature, and dissolved in N,N-dimethylformamide to obtain a mixed solution;

[0013] S2. Add benzotriazole-1-yl-oxytripyrrolidinophosphine hexafluorophosphate, triethylamine and 1-pyrenecarboxamine hydrochloride in sequence to the above mixed solution, carry out amidation reaction at room temperature, pour into deionized water to precipitate, and finally freeze-dry to obtain an amphiphilic binder.

[0014] A negative electrode is prepared by mixing active material silicon carbon, a conductive agent and the amphiphilic binder, adding N-methylpyrrolidone and stirring to obtain a uniformly dispersed electrode slurry, coating the electrode slurry on a copper foil, and vacuum drying.

[0015] Preferably, the conductive agent is conductive carbon black, carbon nanotubes, super conductive carbon black or conductive graphite; the mass ratio of the active material silicon carbon, the conductive agent and the amphiphilic binder is (7-8):(1-2):1.

[0016] Preferably, the stirring time is 6 to 8 hours, the vacuum drying temperature is 100 to 120° C., and the vacuum drying time is 12 to 36 hours.

[0017] The negative electrode is used in lithium-ion batteries. The dried electrode is transferred to a glove box filled with argon gas for battery assembly. The lithium sheet in the battery is used as a counter electrode, the electrolyte uses 1.2mmol / L LiPF6 as a solute, the solvent is ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, fluoroethylene carbonate (FEC) and 1wt% ethylene carbonate (VC) as additives, and assembled into a CR2032 button battery.

[0018] Preferably, the negative electrode material of the lithium-ion battery is a silicon-carbon composite material.

[0019] The present invention obtains polylipoic acid-tannic acid by polyphenol-sulfur radical addition reaction between lipoic acid and tannic acid, and then undergoes amidation reaction with 1-pyrenecarboxamide hydrochloride to synthesize an amphiphilic binder. Tannic acid has abundant catechol and pyrogallol groups, as well as good biocompatibility and strong bonding properties; lipoic acid has a biological molecule with a special structure, including two types of dynamic bonds: a dynamic covalent disulfide bond in a five-membered ring and a non-covalent hydrogen bond of a carboxyl group; 1-pyrenecarboxamide hydrochloride is a polycyclic aromatic hydrocarbon structure with a good conjugated system; the amphiphilic binder modified by tannic acid and 1-pyrenecarboxamide hydrochloride improves the mechanical strength of the binder and realizes the cycle stability of the silicon-carbon negative electrode.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The PLT-Y amphiphilic binder of the present invention is prepared by a polyphenol-sulfenyl free radical addition reaction of natural biological small molecules lipoic acid and tannic acid in the absence of solvent, and then an amidation reaction with 1-pyrenecarboxamine hydrochloride to obtain an amphiphilic binder having a three-dimensional network structure, which is beneficial to the transmission of electrons and ions, greatly improves the mechanical properties of the binder, and enables the electrode to maintain good integrity during the cycle process.

[0022] 2. The PLT-Y amphiphilic binder of the present invention has a good affinity for graphite, conductive carbon black and silicon materials. This is because polylipoic acid and tannic acid have a large number of carboxyl and catechol groups, which have a good affinity for silicon. At the same time, 1-pyrenecarboxamide hydrochloride contains a large number of benzene ring functional groups, which are similar to graphite in structure and can easily form π-π conjugation. The combination of the two is conducive to the formation of a coating layer on the surface of the silicon-carbon material.

[0023] 3. The PLT-Y amphiphilic binder of the present invention has the advantages of good dispersibility and strong adhesion to silicon-carbon materials, which can effectively protect the active materials from the influence of the electrolyte, reduce the large-scale generation of SEI film, and significantly improve the electrochemical performance of the silicon-carbon negative electrode of lithium-ion batteries.

[0024] 4. The polylipoic acid-tannic acid obtained by the reaction of lipoic acid and tannic acid of the present invention contains a reversible dynamic covalent disulfide bond that can be reformed after breaking, and the binder is a three-dimensional network structure, which can effectively inhibit the volume expansion of the silicon-carbon negative electrode material during the charge and discharge process of the electrode, so that the silicon-carbon negative electrode exhibits good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a 180° peeling curve of the silicon-carbon negative electrode made of the amphiphilic binder (PLT-Y) in Application Example 1 and the sodium carboxymethyl cellulose (CMC) in Comparative Example 1.

[0026] Figure 2 This is the cycle performance diagram of the Li∥Si / C950@PLT-Y button battery composed of Application Example 1.

[0027] Figure 3 This is a comparison chart of the cycle performance of the Li∥Si / C950@PLT-Y button battery composed of Application Example 1 and the Li∥Si / C950@CMC button battery composed of Comparative Example 1. DETAILED DESCRIPTION

[0028] The content of the present invention is further described below in conjunction with specific examples, but it should not be construed as limiting the present invention. If not specifically indicated, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0029] Example 1

[0030] Under nitrogen atmosphere, 1.25 g of lipoic acid was added to a three-necked flask, heated to 150°C and reacted with magnetic stirring for 10 min, then 0.05 g of tannic acid was added for cross-linking reaction for 0.5 h, the liquid mixture was dissolved in 30 mL of N,N-dimethylformamide solution, 0.2 g of PyBOP, 0.11 mL of triethylamine and 0.05 g of 1-pyrenecarboxamine hydrochloride were added in sequence, amidation reaction was carried out at room temperature for 36 h, the mixture was poured into 200 mL of deionized water to precipitate, and then freeze-dried for 24 h to obtain an amphiphilic binder, abbreviated as PLT-Y.

[0031] Example 2

[0032] Under nitrogen atmosphere, 4 g of lipoic acid was added to a three-necked flask, heated to 120°C and reacted with magnetic stirring for 10 min, then 0.24 g of tannic acid was added for cross-linking reaction for 1 h, the liquid mixture was dissolved in 80 mL of N,N-dimethylformamide solution, 0.6 g of PyBOP, 0.4 mL of triethylamine and 0.2 g of 1-pyrenecarboxamine hydrochloride were added in sequence, and amidation reaction was carried out at room temperature for 36 h, poured into 500 mL of deionized water to precipitate, and then freeze-dried for 24 h to obtain an amphiphilic binder, abbreviated as PLT-Y.

[0033] Application Example 1

[0034] 1. The active material silicon carbon, the conductive agent SuperP, and the amphiphilic binder of Example 1 were dissolved in a 5wt% amphiphilic binder solution prepared with N-methylpyrrolidone, mixed at a mass ratio of 8:1:1, and then 100-1000mL of N-methylpyrrolidone was added and stirred in a degassing mixer to obtain a uniformly dispersed electrode slurry. The electrode slurry was coated on a copper foil, vacuum dried at 120°C for 12h, and cut into a circular negative electrode sheet with a diameter of 12mm.

[0035] 2. The dried negative electrode sheet was transferred into a glove box filled with argon, and the lithium sheet was used as the counter electrode. The electrolyte used a solute of 1.2mmol / L LiPF6, and the solvent was ethylene carbonate (EC) EC and diethyl carbonate (DEC) with a volume ratio of 1:1, 10wt% fluoroethylene carbonate (FEC) and 1wt% ethylene carbonate (VC) as additives, and assembled into a CR2032 button cell, abbreviated as Li∥Si / C950@PLT-Y, and then left to stand for 10h. The static battery was subjected to a constant current test of electrochemical performance in the Xinwei test system.

[0036] Figure 1 180° peeling curve of the silicon-carbon negative electrode made of the amphiphilic binder (PLT-Y) in Application Example 1 and the sodium carboxymethyl cellulose (CMC) in Comparative Example 1. Figure 1It can be seen that the PLT-Y binder has a stronger adhesion to the silicon-carbon material, which is beneficial to alleviate the volume expansion of the silicon-carbon material during the lithium insertion and extraction process and maintain the structural integrity of the electrode. Figure 2 The cycle performance diagram of Li∥Si / C950@PLT-Y button battery composed of application example 1 is shown in Figure 1. Figure 2 It can be seen that the Li∥Si / C950@PLT-button battery composed of the amphiphilic binder (PLT-Y) has a first discharge specific capacity of more than 1100mAh / g at a current density of 285mA / g, a first coulombic efficiency of 79%, and a capacity of 819mAh / g after 100 cycles, showing excellent cycle stability.

[0037] Comparative Example 1

[0038] 1. 0.5 g of sodium carboxymethylcellulose (currently used in commerce, abbreviated as CMC) powder was added to 9.5 g of deionized water to obtain a 5 wt% binder.

[0039] 2. Mix the active material silicon carbon, the conductive agent SupperP and 5wt% of the binder in a mass ratio of 8:1:1, add 100-1000mL of deionized water and stir for 6-8h to obtain a uniformly dispersed electrode slurry, apply the electrode slurry on the copper foil, vacuum dry at 120℃ for 12h, and cut into round electrodes with a diameter of 12mm.

[0040] 3. The electrode was transferred to an argon-filled glove box for battery assembly. The lithium sheet in the battery was used as the counter electrode, the electrolyte was 1.2mmol / L LiPF6 as the solute, ethylene carbonate (EC) and diethyl carbonate (DEC) with a volume ratio of 1:1 as the solvent, 10wt% fluoroethylene carbonate (FEC) and 1wt% ethylene carbonate (VC) as additives, and assembled into a CR2032 button cell, abbreviated as Li∥Si / C950@CMC.

[0041] The CR2032 button cells assembled in Application Example 1 and Comparative Example 1 were placed at 28°C for 10 hours and then subjected to constant current testing of electrochemical performance in a Xinwei test system. The test conditions were: current density 285 mA / g; voltage window 0.01-1.5 V. Figure 3 The figure is a comparison of the cycle performance of the CR2032 button-type battery prepared in Application Example 1 and Comparative Example 1. Figure 3It can be seen that the Li∥Si / C950@CMC button cell prepared in Comparative Example 1 has a capacity decay of 635mAh / g after 100 cycles at a current density of 285mA / g, and the capacity of the Li∥Si / C950@PLT-Y button cell prepared in Application Example 1 remains above 819mAh / g, with a higher discharge capacity and better cycle stability. It can be seen that the amphiphilic binder (PLT-Y) of the present invention can make the silicon-carbon negative electrode exhibit good cycle stability, thereby improving the electrochemical performance of the silicon-based negative electrode of lithium-ion batteries.

[0042] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. An amphiphilic binder for a silicon-based negative electrode of a lithium-ion battery, characterized in that: The amphiphilic binder is abbreviated as PLT-Y. In a nitrogen atmosphere, lipoic acid and tannic acid are heated and stirred at 120-150° C., the resulting mixed solution is dissolved in N,N-dimethylformamide, and then benzotriazole-1-yl-oxytripyrrolidinophosphine hexafluorophosphate, triethylamine and 1-pyrenecarboxamine hydrochloride are added in sequence. After an amidation reaction at room temperature, the mixture is poured into deionized water to precipitate, and finally freeze-dried to obtain the amphiphilic binder.

2. The amphiphilic binder for lithium-ion battery silicon-based negative electrode according to claim 1, characterized in that: The mass ratio of the lipoic acid, tannic acid, benzotriazole-1-yl-oxytripyrrolidinophosphine hexafluorophosphate and 1-pyrenecarboxamine hydrochloride is 1:(0.04-0.12):(0.2-0.36):(0.12-0.4); the mass ratio of the lipoic acid to triethylamine is 1g:(0.08-0.15)mL.

3. The amphiphilic binder for silicon-based negative electrode of lithium-ion battery according to claim 1, characterized in that: The heating and stirring time is 0.5 to 2 hours, the amidation reaction time is 6 to 36 hours, and the freeze-drying time is 12 to 36 hours.

4. The method for preparing an amphiphilic binder for a silicon-based negative electrode of a lithium-ion battery according to any one of claims 1 to 3, characterized in that: The steps include: S1. In a nitrogen atmosphere, lipoic acid is heated and stirred at 120-150° C., and then tannic acid is added to cause a cross-linking reaction, cooled at room temperature, and dissolved in N,N-dimethylformamide to obtain a mixed solution; S2. Add benzotriazole-1-yl-oxytripyrrolidinophosphine hexafluorophosphate, triethylamine and 1-pyrenecarboxamine hydrochloride to the above mixed solution, carry out amidation reaction at room temperature, pour into deionized water to precipitate, and finally freeze-dry to obtain an amphiphilic binder.

5. A negative electrode, characterized in that: The negative electrode is prepared by mixing active material silicon carbon, a conductive agent and the amphiphilic binder according to any one of claims 1 to 3, adding N-methylpyrrolidone and stirring to obtain a uniformly dispersed electrode slurry, coating the electrode slurry on a copper foil, and vacuum drying.

6. The negative electrode according to claim 5, characterized in that: The conductive agent is conductive carbon black, carbon nanotubes, special conductive carbon black or conductive graphite; the mass ratio of the active material silicon carbon, the conductive agent and the amphiphilic binder is (7-8):(1-2):

1.

7. The negative electrode according to claim 5, characterized in that: The stirring time is 6 to 8 hours, the vacuum drying temperature is 100 to 120° C., and the vacuum drying time is 12 to 36 hours.

8. Use of the negative electrode according to any one of claims 5 to 7 in a lithium ion battery.

9. Use of the negative electrode according to claim 8 in a lithium ion battery, characterized in that: The negative electrode material of the lithium-ion battery is a silicon-carbon composite material.

Citation Information

Patent Citations

  • Composite conductive adhesive suitable for silicon-based negative electrode of lithium ion battery

    CN111384398A

  • Composite binder applied to silicon-carbon negative electrode system of lithium ion battery and negative electrode material containing binder

    CN115588742A

  • Adhesive for silicon-based negative electrode of lithium battery and preparation method of adhesive

    CN115651158A

  • Amphiphilic binder for silicon-carbon negative electrode of lithium ion battery as well as preparation method and application of amphiphilic binder

    CN116874647A

  • Supramolecular composite binder for silicon-based negative electrode of lithium ion battery as well as preparation method and application of supramolecular composite binder

    CN116914146A